Evolution of Insolvency Regulations in Romania - Elena Cristina Baciu (CES Working Papers, 2012)
The financial situation of a firm represents a knowledge that is necessary for all stakeholders because they all need to have information about the capacity of the entity to be profitable. The purpose of the study is to examine the evolution of insolvency regulation throughout the years by concentrating on the changes made in laws. The peculiarities of insolvency law influence the way in which the companies cope with their financial difficulties. The number of insolvent companies and the rate of insolvency are values that show the differences between countries and give the possibility to realize a comparison of the regulations in order to establish the aspects that need improvements.
Keywords: G33; K41; 330; insolvency rate; insolvency law; Romania; Eastern Europe Romania